Academic achievement and sports involvement of Malaysian university athletes - Yusof, Aminuddin; Chun, Cheng Chuan; Mohd Shah, Parilah (2013)
This research studied the factors that influence the academic achievement of Malaysian university athletes. The respondents consisted of 156 field hockey players. The Team Socialization Scale (Allen, 1997) was used to measure the relationships between team subculture, parental influence, the learning environment, support systems, financial aid, training factors, academic assistance, socialization, and stress level and academic achievements of student athletes. The findings showed that there is a significant positive relationship between the learning environmental and academic achievements of university athletes. However there is a negative relationship between the support system and academic achievements of university athletes. The study provides suggestions on how to improve the academic achievement of athletes in Malaysian universities.